Improving Listening Ability in English Learning for Students at SMP PGRI 3 Denpasar - Mirsa Umiyati; Aron Meko Mbete; Adi Cerman; Nurdin; Alexsander Loi (Linguistic Community Services Journal, 2022)
There are four common language skills that must be learned and studied continuously. One of the language skills that must be mastered by students is listening. By having based on ability, students will have the ability to express their thoughts and feelings correctly in the context of the situation needed and capture information with the speaker's intent, then respond to the information itself. A child learns a language through listening first. The process of listening, understanding meaning, imitating, and practicing language sound is repeated until the child speaks fluently. The same thing happens to adults when they learn a foreign language. This article describes the lack of listening in English for junior high school students and the appropriateness of teaching English to increase students' interest in developing listening skills. This may be because students' interest in listening skills is not good and the Extensive Listening approach is applied to improve listening skills, which is applied by the teacher in the learning process so that students do not practice listening skills in English. Based on this situation, the aim of this activity is to help build students' interest in improving English listening skills and through an extensive listening and application approach to teaching listening skills to junior high school students. In the process of listening there are five components, namely paying attention, understanding, remembering, and providing feedback or feedback. The object of this PKM activity is SMP PGRI 3 Denpasar, especially for class VIII students. The results of the research in this activity indicate that students are able to master the five components that have been applied in the teaching process of the Extensive Listening approach that is applied in improving students' listening skills and are able to pay attention, and understand, remember, and respond. Thus, in this case, the implementation is carried out with this focus so that learning outcomes can be optimal.